xzp - yzq= Kxyz by lagrange method
This is Lagrange's equation
The auxiliary equation is,
"\\dfrac{dx}{xz}=\\dfrac{dy}{-yz}=\\dfrac{dz}{Kxyz}"
"\\dfrac{dx}{xz}=\\dfrac{dy}{-yz}=>\\dfrac{dx}{x}=-\\dfrac{dy}{y}"
"\\int \\dfrac{dx}{x}=-\\int\\dfrac{dy}{y}"
"\\ln x=-\\ln y+\\ln C_1"
"\\dfrac{dx}{xz}=\\dfrac{dz}{Kxyz}"
"\\dfrac{dx}{xz}=\\dfrac{dz}{Kx(\\dfrac{C_1}{x})z}"
"KC_1\\dfrac{dx}{x}=dz"
"KC_1\\ln x=z+C_2"
"Kxy\\ln x-z=C_2"
Hence, the required general solution is given by
where "\\phi" is an arbitrary function.
Comments
Leave a comment